Self-assembled GLP-1/glucagon peptide nanofibrils prolong inhibition of food intake - Ouberai, Myriam M.; Gomes Dos Santos, Ana L.; Kinna, Sonja; Hornigold, David C.; Baker, David; Naylor, Jacqueline; Liang, Lihuan; Corkill, Dominic J.; Welland, Mark E. (Frontiers in Endocrinology, 2023)
Dual agonist peptides, such as Oxyntomodulin (Oxm), have a number of beneficial effects on nutrition and metabolism including increased energy expenditure and reduced body weight gain. Despite its many advantages as a potential therapeutic agent, Oxm is subjected to rapid renal clearance and protease degradation limiting its clinical application. Previously, we have shown that subcutaneous administration of a fibrillar Oxm formulation can significantly prolong its bioactivity in vivo from a few hours to a few days. In this study, we have applied this strategy to a protease resistant analogue of Oxm, Aib2-Oxm, to improve serum stability of released peptide. We show that in comparison to Oxm, Aib2-Oxm fibrils display a slower elongation rate requiring higher ionic strength solutions, and a higher propensity to dissociate. Upon subcutaneous administration of fibrillar Aib2-Oxm in rodents, a 5-fold increase in bioactivity relative to fibrillar Oxm and a significantly longer bioactivity than free Aib2-Oxm were characterized. Importantly, a decrease in food intake was observed up to 72-hour post-administration, which was not seen for free Aib2-Oxm. This study demonstrates a very promising approach to develop long-lasting formulations for this class of peptides which are highly investigated to treat obesity and diabetes.